Longitudinal outcomes of radiofrequency ablation versus surveillance endoscopy for Barrett's esophagus with low-grade dysplasia. Issue 4 (27th September 2017) - Kahn, A; Al-Qaisi, M; Kommineni, V T; Callaway, J K; Boroff, E S; Burdick, G E; Lam-Himlin, D M; Temkit, M; Vela, M F; Ramirez, F C
SUMMARY: Radiofrequency ablation of Barrett's esophagus with low-grade dysplasia is recommended in recent American College of Gastroenterology guidelines, with endoscopic surveillance considered a reasonable alternative. Few studies have directly compared outcomes of radiofrequency ablation to surveillance and those that have are limited by short duration of follow-up. This study aims to compare the long-term effectiveness of radiofrequency ablation versus endoscopic surveillance in a large, longitudinal cohort of patients with Barrett's esophagus, and low-grade dysplasia. We conducted a retrospective analysis of patients with confirmed low-grade dysplasia at a single academic medical center from 1991 to 2014. Patients progressing to high-grade dysplasia or esophageal adenocarcinoma within one year of index LGD endoscopy were defined as missed dysplasia and excluded. Risk factors for progression were assessed via Cox proportional hazards model. Comparison of progression risk was conducted using a Kaplan–Meier analysis. Subset analyses were conducted to examine the effect of reintroducing early progressors and excluding patients diagnosed prior to the advent of ablative therapy. Of 173 total patients, 79 (45.7%) underwent radiofrequency ablation while 94 (54.3%) were untreated, with median follow up of 90 months. Seven (8.9%) patients progressed to high-grade dysplasia or adenocarcinoma despite ablation, compared with 14 (14.9%) undergoing surveillance ( P  = 0.44). This effect was preserved when patients diagnosed prior to the introduction of radiofrequency ablation were excluded (8.9% vs 13%, P  = 0.68). Reintroduction of patients progressing within the first year of follow-up resulted in a trend toward significance for ablation versus surveillance (11.1% vs 23.8%, P  = 0.053). In conclusion, progression to high-grade dysplasia or adenocarcinoma was not significantly reduced in the radiofrequency ablation cohort when compared to surveillance. Despite recent studies suggesting the superiority of radiofrequency ablation in reducing progression, diligent endoscopic surveillance may provide similar long-term outcomes.